Relationship between bisphenol A and autoimmune thyroid disease in women of childbearing age - Yuan, Ning; Sun, Jianbin; Zhao, Xin; Li, Wei (Frontiers in Endocrinology, 2024)
Background: Autoimmune thyroid disease (AITD) is the main cause of hypothyroidism in women of childbearing age. Bisphenol A (BPA) is an environmental factor affecting AITD. This study aims to investigate relationship between BPA and AITD in women of childbearing age, thereby contributing novel evidence for the prevention of hypothyroidism in this specific demographic.Methods: A total of 155 women of childbearing age were enrolled in this study, including the control group comprised 60 women with euthyroidism and thyroid autoantibodies negativity and the AITD group consisted of 95 women with euthyroidism and at least one thyroid autoantibody positivity.The general information, thyroid function, thyroid autoantibodies, and thyroid ultrasound results of the two groups of women of childbearing age were recorded. Urinary BPA and urinary BPA/ creatinine were detected. The difference of BPA levels between the two groups was compared. logistic regression was used to analyze the correlation between BPA and AITD.The proportion of multiparous and serum thyroid stimulating hormone levels were significantly higher in the AITD group compared to the euthyroid group. Logistic regression analysis revealed that BPA levels did not exhibit a statistically significant association with AITD.Spearman correlation analysis revealed a statistically significant correlation between BPA and urinary iodine levels (r=0.30, P < 0.05), as well as a correlation between urinary BPA and free tetraiodothyronine (FT4) levels (r=0.29, P < 0.05).This study revealed a correlation between urinary BPA levels and FT4 levels. However, it did not establish a relationship between BPA and AITD in women of reproductive age.